Combating Online Radicalization Through Social Counseling Developing Effective Intervention Strategies For Vulnerable Youth In The Digital Age - Pasaribu, Waldimer; Iffah, Izzatul; Muhazzib, Naufal; Kurnia, Asraf (International Journal of Research in Counseling, 2024)
Since social media and other online platforms expose susceptible youngsters to extremist beliefs more frequently, the emergence of online radicalization in the digital age poses serious concerns. With an emphasis on the psychological, sociological, and technological elements that increase teenage vulnerability, this article explores the complex nature of online radicalization. We offer a thorough therapeutic strategy that uses social therapy as its main weapon to address this problem. To equip young people with critical thinking abilities, our strategy incorporates tactics like focused counseling sessions, community engagement programs, and the incorporation of digital literacy instruction. Building supportive environments that build resilience against radical influences is stressed as a function of trustworthy adult figures, including parents, teachers, and community leaders.. In addition to offering a better knowledge of the mechanics of online radicalization, this research attempts to propose practical solutions for protecting young people and encouraging constructive social integration in a world that is becoming more interconnected by the day.